2021
DOI: 10.1021/acs.iecr.1c01742
|View full text |Cite
|
Sign up to set email alerts
|

Combined GCMC, MD, and DFT Approach for Unlocking the Performances of COFs for Methane Purification

Abstract: Covalent organic frameworks (COFs) are promising materials for gas storage and separation; however, the potential of COFs for separation of CH 4 from industrially relevant gases such as H 2 , N 2 , and C 2 H 6 is yet to be investigated. In this work, we followed a multiscale computational approach to unlock both the adsorption- and membrane-based CH 4 /H 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 90 publications
0
21
0
Order By: Relevance
“…Dself;2 and S mem,12 = S ads,12 × S diff,12 , successively. 66 . All in all, these results suggest that MTV-MOFs that are not overly porous (i.e., PLDs <7 Å, surface areas <3000 m 2 g −1 ) can attain high adsorption-based CF 4 /CH 4 separation performances in terms of selectivity, working capacity, and regenerability.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dself;2 and S mem,12 = S ads,12 × S diff,12 , successively. 66 . All in all, these results suggest that MTV-MOFs that are not overly porous (i.e., PLDs <7 Å, surface areas <3000 m 2 g −1 ) can attain high adsorption-based CF 4 /CH 4 separation performances in terms of selectivity, working capacity, and regenerability.…”
Section: Methodsmentioning
confidence: 99%
“…Regenerability of an adsorbent is calculated as . 66 Since all of these metrics, selectivity, working capacity and regenerability, are important to identify the most promising MOF adsorbents, we defined the , where X i and X max denote the value of the individual performance metric X (selectivity/working capacity/regenerability) for material i and the highest value of the individual performance metric X across all materials, respectively. The individual separation performance scores were summed to determine the overall separation performance scores of MOFs and the materials with the highest overall separation performances were assigned the highest adsorbent rankings.…”
Section: Methodsmentioning
confidence: 99%
“…The insight gained from the computational screening of COFs for membrane applications could be of substantial importance for deciding on the next COF filler to be used in experimental MMM studies. Recent computational studies predicted gas separation properties of COF membranes. For example, Yang et al demonstrated that COF-102, -103, -105, and -108 have higher selectivities (11.7, 14, 28.8, and 33.2, respectively) compared to IRMOF-1 and Cu-BTC for membrane-based H 2 /CH 4 separation at 10 bar and 298 K. 295 COF membranes were investigated for CO 2 /N 2 separation at 1 bar and 10 bar, at 298 K, and results showed that CO 2 permeabilities of COF membranes overcome those of MOF membranes, while MOF membranes have higher CO 2 /N 2 selectivities than COF membranes . A computational investigation on the H 2 /CO 2 separation performances of 288 COF membranes at 10 bar and 298 K has shown that COF membranes significantly outperform polymeric membranes due to their H 2 permeabilities ranging from 599 to 1.5 × 10 6 Barrer and H 2 /CO 2 selectivities of up to 4.74 .…”
Section: Introductionmentioning
confidence: 99%
“…H 2 /CO 2 separation performances of 794 hypoCOF membranes were shown to be even superior, with H 2 permeabilities in the range of 9 × 10 5 –5 × 10 6 Barrer and H 2 /CO 2 selectivities between 2.66 and 6.14 . A total of 572 COFs were studied for membrane-based H 2 /CH 4 separation at 1 bar and 298 K, and several COFs with large porosities showed a good combination of H 2 permeability (>10 5 Barrer) and H 2 /CH 4 selectivities up to 4.6 . In contrast to COF membranes, a very limited number of studies, only two, focused on computational modeling of COF/polymer MMMs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation